PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN MITSUBISHI PAJERO SPORT PADA PT. DIPO INTERNASIONAL PAHALA OTOMOTIF PEKANBARU - Yose Sepriansyah; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at PT. Dipo Internasional Pahala Otomotif Pekanbaru is located on Jl. Jend. Sudirman No 230, Tangkerang Tengah, Kec. Marpoyan Damai, Pekanbaru City, Riau. The purpose of this study was to determine the effect of promotion and product quality on consumer purchase interest of Mitsubishi Pajero Sport at PT. Dipo Internasional Pahala Otomotif Pekanbaru partially and simultaneously. In this research, the method used is quantitative descriptive analysis with the SPSS program. The population in this study are all consumers who purchase a Mitsubishi Pajero Sport type car at PT. Dipo Internasional Pahala Otomotif Pekanbaru in the last year, namely 2019, totaled 257 people. Where the samples in this research are consumers of PT. Dipo Internasional Pahala Otomotif Pekanbaru, as many as 93 respondents. To determine the sample using the Slovin formula. Data collection techniques through questionnaires and interviews, types and sources of data using primary data and secondary data, and measurement techniques using a Likert scale.From data analysis which includes validity test, reliability test, simple linear regression analysis, multiple linear analysis, determination analysis and significance test with t test (partial), and f test (simultaneous). The results of this study indicate that the results of the first t test hypothesis testing, promotion of consumer buying interest, namely t (15.827)> t table (1.6617) means that promotion has a significant effect on consumer purchase interest. Second, product quality on consumer buying interest is t count (15.827)> t table (1.6617) which means that product quality has a significant effect on consumer purchase interest. The results of the f-test promotion and product quality have a significant effect on consumer buying interest, namely f count (235.025)> table (3.10). This means that promotion and product quality simultaneously have a significant effect on consumer purchase interest of Mitsubishi Pajero Sport at PT. Dipo Internasional Pahala Otomotif Pekanbaru.Keywords: Promotion, Product Quality, Consumer Purchase Interest